Kajian Antisipasi Defisit Air Daerah Irigasi Sei Paku Pada Kondisi Kering Meteorologis ( Daerah Irigasi Sei Paku, Kecamatan Kampar Kiri, Kabupaten Kampar) - Sudarmanto Sudarmanto; Mudjiatko Mudjiatko; Trimaijon Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Sei paku irrigation area is located in Kampar Kiri District, Kampar Regency, Riau Province, this irrigation area is specifically planned for rice fields with total area of ± 1000 Hectares. Function change from agricultural land into fish ponds and palm plantation resulted potential land decrease to ± 350 Hectares. Uncontrolled water utilization for fish pond, channels leakage and influence of meteorological factors resulted water supply shortage for agricultural land and water deficit for certain month.Analysis of evapotranspiration, effective precipitation, percolation and water replacement are used to determine the value of the rice water requirement of plant and crops planting. Fish pond water demand and oil palm plantations is used as a reduction of the value of intake discharge, which then the rest of discharge will be used as a main rate of flow for fulfilling plants water needs. In March, May and July crop water requirement is greater than the mainstay discharge, then a simulation done by allocation of planting schedule that is 5 group for rice planting and 3 group for crops planting.The results showed that planting schedule can reduce the value of the maximum water deficit in the existing condition that is 0.36 m3 / s to 0.041 m3 / s or decreased 88.61%, but the deficit is still occurs. So it is necessary to do a Long Storage planning with 2000m long, width 5m and 5m depth with a land area of 1.2 hectares which function as water reservoir that can be used to fulfilling the crops water needs on dry meteorological conditions.Keywords: Sei Paku Irrigation Area, water deficit, water balance, critical discharge, weirs, and long storage